On the feasibility of 3-(hydroxyamino)propane1,2-diol as a base filling scaffold in oligonucleotides - Basnagoda, Shehani (My University, 2026)
During the past three decades modified nucleotides and oligonucleotides have emerged in e.g. therapeutics and diagnostics. Depending on the application, modifications are carried out at the sugar, phosphate or base moieties. These modifications can lead to improved enzymatic resistance, binding affinity, biocompatibility, biodistribution and pharmacokinetics. Base filling can be considered as an alternative to enzymatic or automated oligonucleotide synthesis. Base filling involves post synthetic introduction of a nucleobase to an abasic site on the backbone. This approach can be considered an application of dynamic combinatorial chemistry as equilibrium conditions are to be used in the base filling approach (most, but not all, of the reported base filling reactions are dynamic). The aim of this study was to synthesize an oligonucleotide containing a base filling scaffold having a minimal structure for the reversible functionalization of oligonucleotides. The novel building block features a modified sugar phosphate backbone consisting of an oxazolidine ring in place of sugar moiety and an unusual N-O-P phosphodiester linkage instead of a conventional C-O-P linkage. Different synthetic routes were carried out to synthesize the base filling scaffold. First, a phosphoramidite building block featuring the unusual N-O-P linkage was synthesized successfully. But this phosphoramidite was found to be unreactive and thus unsuitable for oligonucleotide synthesis. Therefore, formation of the desired phosphodiester bond was attempted by an alternative strategy, namely coupling the modified monomer with a commercially available nucleoside phosphoramidite to form a dimer, which will be used to study the compatibility of the carbamate protection and the N-O-P linkage with conditions of automated oligonucleotide synthesis and, ultimately, base filling.
Keywords: modified nucleotides; base filling; phosphoramidite; H-phosphonate diester